COVID STRESS IS LEADING CAUSE OF VIRTUAL STUDY- A COMPARISON OF ONLINE LEARNING TO FACE TO FACE LEARNING - Saman Junaid Chattha; Sumera sattar; Yasmeen Tabassum; Rehan Yousaf (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The present era is the era of distress, anxiety and depression due to the wide spreading Corona virus that has disturbed the education system badly. Such situation is the leading cause for online learning because online learning presents more open doors in circumstances where customary training is battling to work. Fruitful online understudies should likewise be propelled, restrained, independent, and rule their time in different correspondence styles. This paper presented the analysis of importance of online classes vs. face to face learning among student during the corona stress. The results of this analysis proved the fact that more student were promoted toward online learning just to overcome their corona stress and to remain safe.